The Role of Teacher Ethics in Developing Student Character in School - Winanjar Rahayu; Era Tazkiyah; Nurul Murtadho; Slamet Arifin (Universitas Pendidikan Ganesha, 2023)
In school, the teacher must be a role model for students with a good attitude during the learning process so that behavioral deviations do not occur, such as bullying against students and co-workers in educational practice. Deviant behaviors can be imitation material for students, which impacts the teacher's low ethics in teaching. This research aims to analyze the roles of good teacher ethics in the growth of students' character and habits. This type of research is qualitative research. The participants in this study were 17 teachers in an elementary school with at least 10 years of teaching experience. They collect data using data collection techniques, documentation, observation, and interviews. Data analysis uses an interactive model from Miles & Huberman, which includes data reduction, data presentation, and concluding. The results of the study show that the teacher's ethics as a role model are shown in their words, attitudes, and personality, such as politeness, discipline, responsibility, tolerance, honesty, and caring for students and others that have been implemented by teachers and have a good influence on student character through habituation. Factors that support student character development include the school community's commitment, curriculum content standards, principal leadership, togetherness, and tolerance. The teacher's ethical values are central values that can be role models for students in communicating and behaving to help grow student character in today's developments.